Corona Pandemic and its Impact on Educational Exclusion of Tribal Students Belonging to Remote Areas of Gujarat (Case Study of Gujarat Vidyapith, Ahmedabad) - Chauhan, Naresh (Vidyapith (વિદ્યાપીઠ), 2024)
Abstract Covid-19 has created a havoc in the entire world. India has also suffered at a high magnitude because of it. The impacts of such a pandemic would be long-lasting. This paper deals with a small segment of the entire disaster such as the impact on educational exclusion. It deals with a Micro-level case study for students studying as postgraduate students in Gujarat Vidyapith, located in Ahmedabad city. The study uses simple survey technic by electronic medium. Data collected on Google form and analysis with simple techniques of descriptive statistics have been employed. The sample covers the geographical area from North to South parts of the entire eastern tribal belt of Gujarat. Though the Tribal community has faced social and economic exclusion by the mainstream throughout the past, the COVID-19 pandemic hit them a lot by occurring circumstances of comparative higher educational exclusion because of online forms of education. The eastern tribal belt of Gujarat has comparatively lower infrastructure of almost all kinds than that of Aggregated Gujarat. Due to poor facilities of higher education, students are forced to prefer residential educational institutes located at far distances. Gujarat Vidyapith, located in Ahmedabad city is also one of the prime preferences for higher education in students belonging to the schedule tribe in the state of Gujarat. On average Gujarat Vidyapith enrolled 80 percent of their students belonging to the scheduled tribe for the last two decades. Almost all of those are residences of the eastern Tribal belts of Gujarat. Due to COVID-19 Students have to leave university and go through online education. No internet connectivity, insufficient economic capacity to purchase internet services as well as electronic gadgets and lack of Steady supply of electricity minimize the reach of their education. The majority of them are facing connectivity problems for online education, they must travel long distances, and climb on hilltops for internet connectivity. None of them succeeded in attending up to 80% of classes. They also face problems with online examinations and oral evaluations as they have no academic environment. They suffer lots of hurdles in their domestic lives. All these factors arose after the COVID-19 pandemic created multiple impacts on educational exclusion for tribal students belonging to remote areas of Gujarat. Thus the excluded groups of tribal students in education got more excluded during the COVID-19 pandemic.